SI TESIS ZEOLIT MOR ROD-ASSEMBLED BEBAS BENIH DAN ORGAN"IK VTA Dt:"A-TAHAP SUHU KRJSTALISASI - Ihsan, Muhammad
Mordenile (\!OR) is a 111(!/llher of ::eolite Hhich is conwwn \' used as an importat11 cuta rst in rarious chemical reactions in the petroleum and petrochemical refining industries such as hydrocracking, hydroisomeri::ation. alf..ylation, refonning. dc11•axing. and dimethylamine production. However, mordenite has a small pore channel tith dimensions o/"2.5 x 5.7 A .it causes di(f'usion harrier regarding to the limited access to the actiw! clzannels, especial(r for reaclions inl'Oh•ing large molecule'\. More m•er coke'l can he formed and MOR ::eolites are susceptible to deactimtion. The prese11ce of hierarcl11cal pore system (micropore -+ mesopore) in MOR ::eolite crystals is a strategy to overcome !his d!{/iJsion prohlem. It can he obtained using l tn approache< . there are the Top-Dom1 and Bollom-Up approaches On a labora£01:'• scale. the Bottom-l../p approach is more desirable than Top-Dov.n because it produce the .\t!OR ::eolite crystal without the precence of de/eels. recent(,•. porous hierarchical \fOR ::eolite can he obtained hy .,ynthesi::ing MOR ::eolite •which has a rod-a'lsemhled morphology. it has a lzierarchical inrerCI)''Ilalline pore system. Some straregies that have heen applied to produce rod-assembled MOR ::colite are the use of organosilane-ha'led seeds and/or mganic compowul\• or bollom-up sur(acta nts. Previously, MOR Hith rod asw:mhled mmphology has heen succeHjully 'lJ'Illhesi ed H'ithout tHing seeds and organic compounds through one c1:1•stalli::atw1z temperarure of 180 °C llowever, it still produced a relatiw!ly wzi(ormity of the si::e of the crystal and there is no report regarding to these. Rational\•, the crystalline si::e inconsistell(l' is cau'\ed hy an impe1j"ect nucleation proce'ls. 0)''\tal grml'th can ocmr rapid \' ajrer the Cf)'Stalline nucleus is formed when synthesis is carried out lirh one C I)'Stalli::ation temperature (Com•entional Constant Temperature Crystalli::ation CTC). Based on this consideration. tlze rod-assembled \lOR ::eolite was S} nlhesi::ed using the tu•o-stage cry'ltalli::ation temperalllre method ( Tu'O-Stage Temperawre Crystalli::ation 1 TSTC). The first srage was carried out at 90 oc {loll• temperawre). /twas known as an aging process that supports the formation of a huge numher of nystal nuclei. The second s1age is mrried out at 170 °C {high temperature), which